A novel histone deacetylase inhibitor W2A-16 improves the barrier integrity in brain vascular endothelial cells - Inoue, Yasuteru; Ren, Yingxue; Zhang, Shuwen; Bamkole, Michael; Islam, Naeyma N.; Selvaraj, Manikandan; Lu, Wenyan; Caulfield, Thomas R.; Li, Yonghe; Kanekiyo, Takahisa (Frontiers in Cellular Neuroscience, 2024)
The maturation of brain microvascular endothelial cells leads to the formation of a tightly sealed monolayer, known as the blood-brain barrier (BBB). The BBB damage is associated with the pathogenesis of age-related neurodegenerative diseases including vascular cognitive impairment and Alzheimer's disease. Growing knowledge in the field of epigenetics can enhance the understanding of molecular profile of the BBB and has great potential for the development of novel therapeutic strategies or targets to repair a disrupted BBB. Histone deacetylases (HDACs) inhibitors are epigenetic regulators that can induce acetylation of histones and induce open chromatin conformation, promoting gene expression by enhancing the binding of DNA with transcription factors. We investigated how HDAC inhibition influences the barrier integrity using immortalized human endothelial cells (HCMEC/D3) and the human induced pluripotent stem cell (iPSC)-derived brain vascular endothelial cells. The endothelial cells were treated with or without a novel compound named W2A-16. W2A-16 not only activates Wnt/β-catenin signaling but also functions as a class I HDAC inhibitor. We demonstrated that the administration with W2A-16 sustained barrier properties of the monolayer of endothelial cells, as evidenced by increased transendothelial electrical resistance (TEER). The BBB-related genes and protein expression were also increased compared with non-treated controls. Analysis of transcript profiles through RNAsequencing in hCMEC/D3 cells indicated that W2A-16 potentially enhances BBB integrity by influencing genes associated with the regulation of the extracellular microenvironment. These findings collectively propose that the HDAC inhibition by W2A-16 plays a facilitating role in the formation of the BBB. Pharmacological approaches to inhibit HDAC may be a potential therapeutic strategy to boost and/or restore BBB integrity.